2005
DOI: 10.1002/eji.200425564
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic overexpression of the Caspase‐8 inhibitor FLIPshort leads to impaired T cell proliferation and an increased memory T cell pool after staphylococcal enterotoxin B injection

Abstract: The cellular homologues of the viral anti-apoptotic v-FLIP proteins exist as a long (c-FLIP L ) and a short (c-FLIP S ) splice variant. While c-FLIP S and v-FLIP are composed solely of two death effector domains, c-FLIP L contains an (inactive) caspase-like domain in addition to these two death effector domains, thereby structurally resembling proCaspase-8. Both c-FLIP L and c-FLIP S suppress apoptosis by inhibiting Caspase-8 activation, although at different levels of pro-Caspase-8 processing. To analyze the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 47 publications
4
20
1
Order By: Relevance
“…Interestingly, the increased proliferation of FasL ⌬Intra T cells is reduced to wild-type levels in the presence of inhibitory CD4 ϩ CD25 ϩ regulatory T cells, 34 which indicates that additional control mechanisms act in vivo. As we did not find obvious differences in the in vivo proliferation of V␤8 ϩ T cells following injection of wild-type and FasL ⌬Intra mice with the superantigen SEB, our data substantiates the notion that regulatory T cells display an inhibitory influence on the increased activation-induced proliferation of FasL ⌬Intra T cells (Oehme et al 35 and data not shown). An alternative explanation for the SEB result builds on the fact that according to several in vitro studies, the influence of FasL reverse signaling on T-cell proliferation is only observable under conditions of suboptimal stimulation.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, the increased proliferation of FasL ⌬Intra T cells is reduced to wild-type levels in the presence of inhibitory CD4 ϩ CD25 ϩ regulatory T cells, 34 which indicates that additional control mechanisms act in vivo. As we did not find obvious differences in the in vivo proliferation of V␤8 ϩ T cells following injection of wild-type and FasL ⌬Intra mice with the superantigen SEB, our data substantiates the notion that regulatory T cells display an inhibitory influence on the increased activation-induced proliferation of FasL ⌬Intra T cells (Oehme et al 35 and data not shown). An alternative explanation for the SEB result builds on the fact that according to several in vitro studies, the influence of FasL reverse signaling on T-cell proliferation is only observable under conditions of suboptimal stimulation.…”
Section: Discussionsupporting
confidence: 90%
“…By contrast, c-FLIPs (short form) and K13 v-FLIP Tg mice do not exhibit any abnormalities in thymic development (8,25). We found that thymic development as determined by the percentages of CD4 Ϫ 8 Ϫ DN, CD4 ϩ 8 ϩ DP, and CD4 Ϫ 8 ϩ or CD4 ϩ 8 Ϫ SP thymocytes and thymic cellularity was normal in the Tg mice (Fig.…”
Section: Normal Lymphocyte Development and Lymphoproliferation In Thementioning
confidence: 65%
“…A previous study demonstrated that overexpression of c-FLIP S in T cells inhibited T cell proliferation (23). To rule out the possibility that the impaired CD8 ϩ effector T cell differentiation observed in c-FLIP L Ϫ/Ϫ mice was due to inhibition by the c-FLIP S BAC tg, we compared CD8 ϩ effector T cell development in c-FLIP f/f and c-FLIP f/f c-FLIP S BAC tg mice.…”
Section: Impaired Effector T Cell Development In C-flip L ϫ/ϫ Micementioning
confidence: 99%